Contribution of Dynamic Rheology Coupled to FTIR and Raman Spectroscopies to the Real-Time Shaping Ability of a Hyperbranched Polycarbosilane - Nilesh Dhondoo; Julie Cornette; Sylvie Foucaud; Maggy Colas; Romain Lucas-Roper (Molecules, 2023)
In the field of non-oxide ceramics, the polymer-derived ceramic (PDC) approach appears to be very promising, especially for obtaining easily shaped and homogeneous materials in terms of structure and composition. However, in order to reach a suitable form during the process, it is often necessary to study the rheology of preceramic polymers while they are modified during polymerisation or crosslinking reactions. Given this need in the understanding of the real-time rheology of macromolecules during their synthesis, a rheometer coupled with both an infrared spectrometer and a Raman probe is described as a powerful tool for monitoring in situ synthesised polycarbosilanes. Indeed, this original device allows one to control the viscosity of a hyberbranched polycarbosilane from defined difunctional and tetrafunctional monomers. Meanwhile, it links this evolution to structural modifications in the macromolecular structure (molar masses, dispersity and conformation), based on SEC-MALS analyses, synchronised by the monomer conversion determined by using Raman and infrared spectroscopies, a common denominator of the aforementioned instrumental platform.